Application of Aromatic Substituted 2,2,2-Trifluoro Diazoethanes in Organic Reactions - Zhang, Cai (Current Organic Chemistry, 2022)
This review provides an overview of metal-, nonmetal-, light-, or catalyst freepromoting reactions of aromatic substituted 2,2,2-trifluoro diazoethanes with organic molecules for the synthesis of trifluoromethyl-substituted compounds. Several approaches will be reviewed and divided into (i) copper-, iron-, Trop(BF4)-, B(C6F5)3-, light-, or rhodiumpromoted reactions of aromatic substituted 2,2,2-trifluoro diazoethanes with silanes, amines, mercaptans, phosphonates, p-cyanophenol, benzoic acid, diphenylphosphinic acid, boranes and nBu3SnH, (ii) rhodium-catalyzed reactions of aromatic substituted 2,2,2-trifluoro diazoethanes with amides and phenylhydroxylamine, (iii) copper-, rhodium-, silver-, and lightcatalyzed reactions of aromatic substituted 2,2,2-trifluoro diazoethanes with alkynes, (iv) palladium-, copper-, rhodium- and iron-catalyzed reactions of aromatic substituted 2,2,2-trifluoro diazoethanes with alkenes, (v) BF3·OEt2-, copper-, tin- or TBAB-catalyzed reactions of aromatic substituted 2,2,2- trifluoro diazoethanes with HF·Py, (difluoroiodo)toluene (p-TolIF2), TMSCF3, AgSCF3, TMSCF2Br or 1,3- dicarbonyl compounds, (vi) palladium-, copper-, gold/silver- or rhodium-catalyzed reactions of aromatic substituted 2,2,2-trifluoro diazoethanes with indoles, benzene compounds or pyridines, and (vii) palladium-catalyzed reaction of aromatic substituted 2,2,2-trifluoro diazoethanes with benzyl or allyl bromides.
Keywords: alkynes